Uji Validitas Dan Reliabilitas Alat Ukur Penelitian : Quesionnaire Emphaty - Pramuaji, Krisan Andreas; Loekmono, Lobby (Universitas Pendidikan Ganesha, 2018)
To find out the quality of the findings of the research is very important on the quality of the data collected by researchers. Instruments / measuring instruments are tools used to collect data or measure variables in a study. An instrument / measuring instrument that is recognized as good if the measuring instrument is valid and reliable. To read the measuring instrument, it can be proved wrong through the SPSS for window program. To find and prove the coefficient value of the validity of the instrument / measuring instrument using the Pearson product moment formula. With the criteria for each item> 0.3. While to measure the reliability of an instrument / measuring instrument can be proven using the Cronbach Alpha formula. The empathy instrument that is tried, can be questioned has a high level of validity and the tool is related to measurements that are in accordance with the required and this instrument also has a high level of reliability, can be accounted for, reliable and stable.Â Keywords: validity, reliability, empathy questionaire